The Impact of Yoga on the Immune System of Cancer Patients: A Scoping Review of Current Evidence - Giridharan, S; Bhana, Rajanee (International Research Journal of Ayurveda & Yoga, 2024)
Background: Cancer is a growing problem worldwide, and new strategies for its management and treatment are required. The immune system plays a crucial role in cancer progression and the response to treatment. Recent studies have demonstrated that practicing yoga can positively affect the immune system. This review aimed to examine the impact of yoga on immune parameters in patients with cancer. Methods: We conducted literature searches across several scientific databases for trials published from 2014 to 2023. Studies were selected based on specific criteria, including randomized controlled trials involving yoga interventions with quantitative outcome assessments. Results: Eight studies met our inclusion criteria. These findings suggest that practicing yoga can significantly improve immune function in patients with cancer. Key findings include reductions in inflammatory cytokines, improvements in natural killer cell counts, and modulated gene expression related to immune cell survival. Specific studies have demonstrated benefits in reducing stress and fatigue, enhancing overall quality of life (QoL), and immunological benefits. Conclusion: This review indicates that yoga interventions hold substantial promise in enhancing immune function and overall QoL in patients with cancer.